Impact of Abrupt Late Holocene Monsoon Climate Change on the Status of an Alpine Lake in North China. Issue 4 (22nd February 2020) - Cheng, Bei; Liu, Jianbao; Chen, Shengqian; Zhang, Zhiping; Shen, Zhongwei; Yan, Xinwei; Li, Fanyi; Chen, Guangjie; Zhang, Xiaosen; Wang, Xin; Chen, Jianhui
Abstract: The late Holocene is generally regarded as an interval of monsoon recession and decreased precipitation in North China. However, the extent to which this affected the status of lakes in North China is unclear. In the study, we analyzed multiple proxies (δ 13 C, magnetic susceptibility [χlf ], and exogenous element concentrations) from Lake Mayinghai, an undisturbed alpine lake in North China. We also compared the results with previously published paleoenvironmental records from the Chinese Loess Plateau. We aimed to determine the extent of the influence of variations in the East Asian summer monsoon (EASM) on the status of Lake Mayinghai during the late Holocene. The results demonstrate that negative δ 13 C values at Lake Mayinghai correspond to high sedimentary tree pollen content and high reconstructed precipitation, indicating that variations in δ 13 C likely reflect variations in vegetation and the EASM in North China. A comparison of the δ 13 C record with other proxies from the same core reveals an abrupt change in the EASM at ~3 kyr before present (BP), which is also evident in other regional climate records from the Chinese Loess Plateau. The rapid decline in EASM intensity at ~3 kyr BP is also consistent with changes in the status of Lake Mayinghai, Lake Gonghai, Lake Ganhai, and Lake Daihai, in that these lakes underwent an abrupt retreat after 3 kyr BP, demonstrating that the rapid decline in EASM intensity at ~3 kyr BP had a large impact on lake evolution in North China. Key Points: There is widespread evidence of an abrupt change in the EASM at ~3 kyr BP The rapid decline of EASM intensity at 3 kyr BP had a large influence on the integrated lake status in North China Ongoing global climatic warming will further dominate changes in the status of lakes in North China